Mono-specific facies of Parazoanthus axinellae in Luiz Saldanha Marine Park. (26th June 2015) - Gomes-Pereira, J.N.; Vasco-Rodrigues, N.; Afonso, A.; Albuquerque, M.; Berecibar, E.; Bernardes, L.; Calado, A.; Castanheira, A.; Tojeira, I.; Tempera, F.; Dias, F.C.; Santos, R.S.; et al.
Abstract : We report the first mono-specific facies of Parazoanthus axinellae from the western Portuguese coast. The habitat was recorded using a MiniRov Observer on a large outcrop at ca. 55–60 m in the Luiz Saldanha Marine Park. A method to estimate the maximum uncertainty of the ROV position is illustrated and the occurrence of the facies is discussed.